THE SCHOOL PERFORMANCE EVALUATION OF SEKOLAH INDONESIA KUALA LUMPUR - Pardosi, Ariani Selviana (Journal of Education Research in Administration and Management (JERAM), 2017)
School is an institution of education that managed by many stakeholders. The core of school service provides a public service in education. As a public servicer, school must take a serious effort to maintain its performance .Performance evaluation is kind of effort to maintain and develop quality of service. School evaluation performance should bean integrated evaluated. Balanced scorecard one of the some performance approaches that focusing in many areas- not only financial perspective but also costumer, internal business process , and growth and learning perspective. Balanced scorecard have been approved as an effective approaches in bussines institution. The result of evaluation give a complete and integrated information. Balanced scorecard should be an effective approaches of school performance as well.